2019
DOI: 10.1111/nuf.12396
|View full text |Cite
|
Sign up to set email alerts
|

Nurse educators’ perceived organizational factors affecting their psychological empowerment: An exploratory qualitative study

Abstract: Background Organizational culture affects nurse educators’ psychological empowerment. Limited research exists on the organizational culture and psychological empowerment in nursing educational environments and about the type of organizational factors affecting nurse educators’ psychological empowerment. Aim To explore nurse educators’ perceived organizational factors that affect their psychological empowerment. Methods A qualitative descriptive exploratory study was drawn from a larger sequential exploratory‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Third, in order to answer the question of how teacher psychological empowerment is associated with organisational factors, we found that all 7 studied organisational factors are related to teacher psychological empowerment in general and individual dimensions of psychological empowerment. This confirms the thoughts of other researchers (e.g., Zeb et al 2019) about the importance of organisational factors for teacher psychological empowerment and suggests that it would be more appropriate to analyse teacher psychological empowerment not at the micro, but at the macro level, taking into account the school organisational factors as an important context, promoting, facilitating psychological empowerment process or hindering it (Lee and Nie 2014). In addition, it also reflects the vision that the processes taking place in the school should be viewed as a whole, strengthening the complex integrated perspective of different organisational factors' impact on teacher psychological empowerment (Kang et al 2021).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Third, in order to answer the question of how teacher psychological empowerment is associated with organisational factors, we found that all 7 studied organisational factors are related to teacher psychological empowerment in general and individual dimensions of psychological empowerment. This confirms the thoughts of other researchers (e.g., Zeb et al 2019) about the importance of organisational factors for teacher psychological empowerment and suggests that it would be more appropriate to analyse teacher psychological empowerment not at the micro, but at the macro level, taking into account the school organisational factors as an important context, promoting, facilitating psychological empowerment process or hindering it (Lee and Nie 2014). In addition, it also reflects the vision that the processes taking place in the school should be viewed as a whole, strengthening the complex integrated perspective of different organisational factors' impact on teacher psychological empowerment (Kang et al 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, interpersonal working relationships affect teacher psychological empowerment. The research results show that the lack of collaboration and support negatively influence teacher psychological empowerment, while institution and educator greater engagement in intra and inter collaboration foster the psychological empowerment of educators (Zeb et al 2019). The study of Khany and Tazik (2016) confirms this regularity-trust in principal and colleague is indirectly related to job satisfaction through teacher psychological empowerment.…”
Section: The Role Of the Organisational Factors For Fostering Teacher...mentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, Hsu and Chen (2017) supported that organizational innovation climate and psychological capital significantly and directly affect innovative employee behaviour. Similaryly, Zeb et al (2019) found that organizational culture and job satisfaction among nurses only be addressed with the enhancing psychological empowerment factor. Consequently, thus, we proposed that psychological empowerment mediates the impact of ethical climate on job performance and innovative behaviour among nurses.H1 Psychological empowerment is a mediator between ethical climate and job performance.H2 Psychological empowerment is a mediator between ethical climate and Innovative behaviour.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Empirical studies examining the mediating role of psychological empowerment in the presence of structural empowerment as an independent variable also supported the positive relationship between structural and psychological empowerment [1,6,10,13]. In addition, Zeb et al [37] identifed three main themes that infuence nurse educators' psychological empowerment: poor organizational structure, dynamics of educators-academic administrators' relations, and educational tools and physical environment.…”
Section: Infuences Of Structural Empowerment and Demographicmentioning
confidence: 93%